2019
DOI: 10.1111/1462-2920.14774
|View full text |Cite
|
Sign up to set email alerts
|

Life in the dark: far‐red absorbing cyanobacteria extend photic zones deep into terrestrial caves

Abstract: Summary Chlorophyll (Chl) f and d are the most recently discovered chlorophylls, enabling cyanobacteria to harvest near‐infrared radiation (NIR) at 700–780 nm for oxygenic photosynthesis. Little is known about the occurrence of these pigments in terrestrial habitats. Here, we provide first details on spectral photon irradiance within the photic zones of four terrestrial cave systems in concert with a detailed investigation of photopigmentation, light reflectance and microbial community composition. We frequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 45 publications
3
32
0
1
Order By: Relevance
“…Hence, the selective benefit of employing Chl d , Chl f , and red-shifted phycobilins in oxygenic photosynthesis appears more related to the capability of exploring special ecological niches in the shadow of other oxygenic phototrophs ( Ohkubo and Miyashita, 2017 ; Kühl et al, 2005 ). The present study and the few other studies of natural habitats (Table S1) demonstrate that a key trait of such cyanobacteria is the formation of biofilms in strongly shaded environments below other algae, cyanobacteria or terrestrial plants, or in the twilight zone of caves ( Behrendt et al, 2019 ). It remains to be explored to what extent the presence of cyanobacteria with FaRLiP-capability or constitutive high Chl d levels play a role for overall photosynthetic productivity in such habitats.…”
Section: Resultssupporting
confidence: 63%
See 2 more Smart Citations
“…Hence, the selective benefit of employing Chl d , Chl f , and red-shifted phycobilins in oxygenic photosynthesis appears more related to the capability of exploring special ecological niches in the shadow of other oxygenic phototrophs ( Ohkubo and Miyashita, 2017 ; Kühl et al, 2005 ). The present study and the few other studies of natural habitats (Table S1) demonstrate that a key trait of such cyanobacteria is the formation of biofilms in strongly shaded environments below other algae, cyanobacteria or terrestrial plants, or in the twilight zone of caves ( Behrendt et al, 2019 ). It remains to be explored to what extent the presence of cyanobacteria with FaRLiP-capability or constitutive high Chl d levels play a role for overall photosynthetic productivity in such habitats.…”
Section: Resultssupporting
confidence: 63%
“…The persisting textbook notion that oxygenic photosynthesis is mainly driven by visible wavelengths of light (400-700 nm) and chlorophyll (Chl) a as the major photopigment is challenged. Recent findings indicate that cyanobacteria with red-shifted chlorophylls and phycobilins capable of harvesting near infrared radiation (NIR) at wavelengths >700-760 nm and exhibiting a pronounced plasticity in their photoacclimatory responses ( Gan et al, 2014 ; Gan and Bryant, 2015 ) are widespread in natural habitats ( Gan et al, 2015 ; Zhang et al, 2019 ; Behrendt et al, 2019 ). Besides the Chl d -containing cyanobacterium Acaryochloris marina , which was originally isolated from tropical ascidians ( Miyashita et al, 2014 ) but has now been found in many other habitats ( Behrendt et al, 2011 ; Zhang et al, 2019 ), the discovery of Chl f ( Chen et al, 2010 ) and its occurrence in many different cyanobacteria ( Gan et al, 2015 ) has triggered a substantial amount of research on the biochemistry and molecular physiology of Chl f -containing cyanobacterial strains ( Airs et al, 2014 ; Allakhverdiev et al, 2016 ; Chen, 2014 ; Ho et al, 2016 ; Nürnberg et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…were present limestone caves, in complete darkness. These bacteria can photosynthesize using near‐infrared radiation and chlorophyll d and f to generate energy (Behrendt et al ., 2020). A future study on the presence of Cyanobacteria capable of utilizing near‐infrared radiation in the tombs devoid of visible light is needed to elucidate their potential contribution to moonmilk metabolism.…”
Section: Resultsmentioning
confidence: 99%
“…The unique adaptations to alternative sources of water and low-light conditions inside these caves suggest that microbial life on Mars may have used similar strategies and similar hygroscopic materials in order to photosynthesize in a protected cave environment (Figure 7), where different types of chlorophyll-like molecules may be used for this end (Behrendt et al, 2020), in one of the last refuge potentially used by life in an ever-drying planet.…”
Section: The Two Most Martian-like Ecosystems Of the Atacama Desert The Coastal Rangementioning
confidence: 99%